Canary girls : a novel [large type] - Chiaverini, Jennifer (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
During World War I, April Tipton, a nineteen-year-old former maid, takes a job at Thornshire Arsenal filling shells, where she befriends the wife of a star footballer and the decides to join the ladies' football club.